Heterogeneous Charge Transfer at the Amorphous Carbon/Solution Interface: Effect on the Spontaneous Attachment of Aryldiazonium Salts - Colavita, Paula (My University, 2013)
The chemisorption of aryldiazonium salts is one of the most versatile reactions for the modification of carbon surfaces; in this work we investigated the spontaneous chemisorption of aryldiazonium salts at amorphous carbons of differing graphitic content in order to relate surface reactivity to the valence electronic properties of aryldiazonium cations and carbon surfaces. Two structural isomers that differ by their redox potential were chosen for our studies: 4-Nitronaphthalenediazonium tetrafluoroborate(4NND) and 5-nitronaphthalenediazonium tetrafluoroborate (5NND). The adsorption of 4NND and 5NND was studied in situ via attenuated total internal reflectance Fourier Transform infrared spectroscopy (ATR-FTIR) and ex situ via electrochemistry on two types of graphitic amorphous carbons (a-C), containing 80% and 100% trigonally bonded carbon centers. These two forms of carbon were characterized via Electrochemical Impedance Spectroscopy (EIS) and the more graphitic surface was found to display a heterogeneous charge transfer rate constant two orders of magnitude larger than the less graphitic surface. This was consistent with Ultraviolet Photoelectron Spectroscopy (UPS) results showing that the density of occupied states near the Fermi level is higher for the more graphitic substrate. In situ and ex situ studies of adsorption ratesshow that, on the less graphitic a-C surface, differences in adsorption rate could be explained based on the reduction potentials of the two aryldiazonium cations. However, on the more graphitic surface we observed nodifference in adsorption rates or yields between the two isomers, thus suggesting that spontaneous electron transfer is not rate determining at these surfaces. Gerischer-Marcus theory was used in order to explain the differences in charge transfer rates between the two carbons and to interpret observed differences in aryldiazonium adsorption rates at these substrates. Finally, our results are discussed in light of the current proposed mechanism of aryldiazonium chemisorption.
PUBLISHED
Keywords: Aryldiazonium; Marcus theory; Polycyclic aromatic hydrocarbon; PAH; Electron transfer; Amorphous carbon